2020
DOI: 10.7554/elife.51295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of slit3 as a locus affecting nicotine preference in zebrafish and human smoking behaviour

Abstract: To facilitate smoking genetics research we determined whether a screen of mutagenized zebrafish for nicotine preference could predict loci affecting smoking behaviour. From 30 screened F3 sibling groups, where each was derived from an individual ethyl-nitrosurea mutagenized F0 fish, two showed increased or decreased nicotine preference. Out of 25 inactivating mutations carried by the F3 fish, one in the slit3 gene segregated with increased nicotine preference in heterozygous individuals. Focussed SNP analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 105 publications
1
21
0
Order By: Relevance
“…Defective habituation is also associated with neuropsychiatric disorders, such as schizophrenia [ 23 ]. In zebrafish assays of response to acoustic startle, a progressive reduction in mean distance travelled with stimulus number gives an indication of habituation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Defective habituation is also associated with neuropsychiatric disorders, such as schizophrenia [ 23 ]. In zebrafish assays of response to acoustic startle, a progressive reduction in mean distance travelled with stimulus number gives an indication of habituation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the possibility of a binary mixture toxicity associated with PTU and the varying glyphosate concentrations cannot be completely excluded. Regarding our behavioral analyses we here acknowledge that, while 4 dpf zebrafish embryos do not respond to an acoustic startle, 5 dpf zebrafish do (Best et al, 2008;Bhandiwad et al, 2013;Zeddies and Fay, 2005) and they were used by others when testing chemicals (García-González et al, 2020;Wolman et al, 2011).…”
Section: Study Limitations and Conclusionmentioning
confidence: 99%
“…Conditioned place preference (CPP), where drug exposure is paired with specific environmental cues, is commonly used as a measure of drug-induced reinforcement and reward [56]. Previous studies have shown that zebrafish show a robust CPP to nicotine [5760] . Here, we show developmental exposure to 0.15 μM nicotine lead to altered sensitivity of the drug-induced reinforcement and reward as measured in CPP (See [57] for methodology on the CPP assay). Fish that were not developmentally treated with nicotine showed a small increase in preference when conditioned with 5 μM nicotine.…”
Section: Figure S3mentioning
confidence: 99%
“…Conditioned place preference (CPP), where drug exposure is paired with specific environmental cues, is commonly used as a measure of drug-induced reinforcement and reward [56]. Previous studies have shown that zebrafish show a robust CPP to nicotine [5760] .…”
Section: Figure S3mentioning
confidence: 99%
See 1 more Smart Citation